A Christmas legacy [large type] : a novel - Perry, Anne (Perry, Anne. Christmas novels ;, 2021)
"After her friend gets unceremoniously fired with no references right before the holidays, Gracie takes the recently-vacated job herself to try and figure out what happened, in the latest novel of the series following A Christmas resolution"--